Implementasi E-Modul Mitigasi Bencana Banjir untuk Meningkatkan Literasi Lingkungan Siswa SMPN Kota Bengkulu - Elda Handayani Elda; Afrizal Mayub; M. Sutarno (PendIPA Journal of Science Education, 2024)
[Implementation of Flood Mitigation E-Module to Improve The Junior High School Students' Environtment Literacy] This research’s purpose was to describe the differences of the students’ environment literacy before the students take part in learning using the flood disaster mitigation e-module and after they take part in learning using the flood disaster mitigation e-module. This research was conducted on 30 students of class VII at SMPN 2 Bengkulu using the one group pretest-posttest design method. The improvement of environment literacy is measured by giving the students a pretest-posttest. The pretest is carried out before learning using the flood disaster mitigation e-module to improve the students' environment literacy. Furthermore, after completing learning using the flood disaster mitigation e-module, the students were given a posttest. The students' environment literacy in this study covered three domains, namely knowledge, cognitive skills, and environmental care attitudes. The result of this research showed that there were differences in students' environment literacy before and after the students took part in learning with the flood disaster mitigation e-module, it can be seen from the overall environmental literacy N-Gain results of 0.6 in the medium criteria. Beside that, a significance value of 0.000 <0.05 was obtained, it was mean that there was a significant influence using the flood disaster mitigation e-module in increasing students' environmental literacy.